Tactile acuity of fingertips and hand representation size in human Area 3b and Area 1 of the primary somatosensory cortex - J. Härtner; S. Strauss; J. Pfannmöller; M. Lotze (NeuroImage, 2021)
Intracortical mapping in monkeys revealed a full body map in all four cytoarchitectonic subdivisions of the contralateral primary somatosensory cortex (S1), as well as positive associations between spatio-tactile acuity performance of the fingers and their representation field size especially within cytoarchitectonic Area 3b and Area 1. Previous non-invasive investigations on these associations in humans assumed a monotonous decrease of representation field size from index finger to little finger although the field sizes are known to change in response to training or in disease. Recent developments improved noninvasive functional mapping of S1 by a) adding a cognitive task during repetitive stimulation to decrease habituation to the stimuli, b) smaller voxel size of fMRI-sequences, c) surface-based analysis accounting for cortical curvature, and d) increase of spatial specificity for fMRI data analysis by avoidance of smoothing, partial volume effects, and pial vein signals.We here applied repetitive pneumatic stimulation of digit 1 (D1; thumb) and digit 5 (D5; little finger) on both hands to investigate finger/hand representation maps in the complete S1, but also in cytoarchitectonic Areas 1, 2, 3a, and 3b separately, in 21 healthy volunteers using 3T fMRI. The distances between activation maxima of D1 and D5 were evaluated by two independent raters, blinded for performance parameters. The fingertip representations showed a somatotopy and were localized in the transition region between the crown and the anterior wall of the post central gyrus agreeing with Area 1 and 3b. Participants were comprehensively tested for tactile performance using von Freyhair filaments to determine cutaneous sensory thresholds (CST) as well as grating orientation thresholds (GOT) and two-point resolution (TPD) for spatio-tactile acuity testing. Motor performance was evaluated with pinch grip performance (Roeder test). We found bilateral associations of D1-D5 distance for GOT thresholds and partially also for TPD in Area 3b and in Area 1, but not if using the complete S1 mask. In conclusion, we here demonstrate that 3T fMRI is capable to map associations between spatio-tactile acuity and the fingertip representation in Area 3b and Area 1 in healthy participants.